Analysis-ready optical underwater images collected along OFOS profile SO268/2_160-1 during SONNE cruise SO268/2, Clarion-Clipperton Zone (Pacific Ocean) - Mbani, Benson; Greinert, Jens (In: Mbani, B; Greinert, J (2023): Analysis-ready optical underwater images collected along OFOS profiles during SONNE cruises SO268/1 and SO268/2, Clarion-Clipperton Zone (Pacific Ocean) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.957274, 2023)
This dataset comprises a sequence of analysis-ready seafloor optical images of the Clarion-Clipperton Zone (CCZ) in the Pacific Ocean. These images have been pre-processed and are directly usable by the marine imaging community. The raw images were acquired along 12 OFOS (camera) deployment tracks, during SONNE expeditions SO268/1 and SO268/2 to the Mn-nodule covered deep seabed areas of the CCZ in the Pacific Ocean; the raw images have been published here https://doi.org/10.1594/PANGAEA.935856. We subjected these raw images through a series of transformations aimed at correcting for the degradation in visual quality that is typical of underwater images of the deep sea. In particular, the transformations we applied to the raw images include: correction for illumination drop-off radially from the image center towards the edges; contrast enhancements though contrast limited adaptive histogram equalization; color normalization to correct for uneven scene brightness among individual images; and finally, standardization of the varying spatial footprint size due to the inability of the imaging platform (OFOS) to maintain a consistent altitude above the seafloor. Therefore, the provided images are ready to be used in seafloor substrate classification studies.
Keywords: Clarion Clipperton Fracture Zone; OFOS; optical camera; Seafloor images; Underwater images